Faktor–Faktor Yang Mempengaruhi Kinerja Guru SMA Negeri Di Nusa Tenggara Barat (NTB) - * Raddana (DIA: Jurnal Administrasi Publik, 2013)
In accordance with the demands of professionalism of teachers, the government issued Law No. 14 Year 2005 on Teachers and Lecturers. Teachers are professional educators with the primary task of educating, teaching, guiding, directing, training, assessing and evaluating students in early childhood education, formal education, primary education and secondary education. Population were all state high school teachers in NTB who have followed and passed the certification of teachers, a total of 2499 teachers, with respondents    educator (Teachers who have received the realization allowance educator certification in the province). From the test results for the model in this study, the Generalized Least Square Estimation (GLS), the analysis of structural equation model (SEM), proportional random sampling method and software support Amos 20, at 200 State High School teacher respondents who had graduated and certified educator, able to explain the influence of teacher certification, teacher competence, teacher motivation and job satisfaction of teachers on state high school teacher performance in NTB. The results showed that: teacher certification significantly affect teachers' competence and motivation of teachers at state high schools in NTB, it indicates that the certification program, encouraging increased competence and motivation of teachers. Certification of teachers do not significantly affect job satisfaction, it indicates that the teacher certification program, there is currently satisfied teachers make state high schools in NTB. Competence of teachers work significantly affect job satisfaction and teacher performance. Teacher job satisfaction significantly affect the performance of teachers. Teacher certification significant indirect effect on teacher performance through motivation as an intervening variable. The results of this study indicate that the increase in performance of the teachers do not arise directly as a result of teacher certification, but the performance of teachers will increase preceded the increase in work motivation of teachers. Teacher certification is not significant indirect effect on the performance of teachers through teacher job satisfaction. The results of this study indicate that the increase in the performance of teachers is not related to the certification of teachers. Teacher performance will be preceded by rising up work motivation and competence of teachersKeywords : teacher certification, teacher competence, teacher motivation, teacher satisfaction, teacher performance.